Exploring new narratives for preserving and presenting the heritage resources of the Kingdom of Saudi Arabia - Alrawaibah, Alaa (2017)
In this thesis, I discuss aspects related to heritage management practices in the Kingdom of Saudi Arabia (KSA). The major aims of this thesis are to introduce new narratives through which the history of the KSA from the pre-Islamic era to the present day can be better interpreted and to develop the interest of the entire community and get locals involved in some of the archaeological practices. I review the current situation of the heritage resources in the KSA, visit selective case studies, and investigate experiences curated by the Saudi Commission for Tourism and National Heritage (SCTH) experiences. I analyse their practices and the ways they represented and interpreted the KSA’s history in museums, both nationally and internationally. I also discuss issues of community involvement and the possibilities of building a bridge between these heritage resources and the surrounding communities. Additionally, the promising results from the community survey that I distributed indicate that the community is interested in getting involved in community archaeology activities, but unfortunately this interest is currently ignored by the SCTH. In conclusion, I examine key archaeological case studies within different regions of KSA and produced three different themes to represent the ancient history of my case studies in the KSA museums. Subsequently, I make recommendations for future approaches to cultural-resources tourism that is associated with the management and representation of KSA’s museums and archaeological sites.